Child Welfare Responses Linked to Subtypes of Exposure to Intimate Partner Violence: Evidence From the Canadian Incidence Study of Reported Child Abuse and Neglect. Issue 13 (July 2020) - Gonzalez, Andrea; MacMillan, Harriet; Tanaka, Masako; Jack, Susan M.; Tonmyr, Lil
Children exposed to intimate partner violence (CE-IPV) are at increased risk for later health and social difficulties. To date, studies have primarily focused on CE-IPV as a unitary construct; this may lead to the mistaken assumption that all subtypes of CE-IPV (i.e., exposure to direct or indirect physical abuse, or exposure to emotional abuse) are equally harmful requiring similar responses from child welfare services. The purpose of this study was to examine child welfare responses by CE-IPV subtype in a large Canadian child welfare sample. Using data from the Canadian Incidence Study of Reported Child Abuse and Neglect–2008 ( N = 2, 184), we examined child welfare responses to CE-IPV subtypes or their co-occurrence. Information was obtained from child welfare workers' reports. Cases with co-occurring subtypes of CE-IPV were more likely to be substantiated and involved multiple incidents compared with that with single CE-IPV subtypes. Cases with direct physical CE-IPV and co-occurring CE-IPV were also more likely to remain open and have an application considered or made to child welfare court. Exposure to emotional IPV was the least likely to warrant interventions by welfare services, including referrals to specialized services. These results suggest that within CE-IPV subtypes, there is evidence of different responses (recommendations and services) once a case has been opened by a worker. Future research is needed to examine the effectiveness of the responses and outcomes for children following child welfare interventions.